Islam and the Middle East The Aesthetics of a Political Inquiry - Abul-Fadl, Mona (International Institute of Islamic Thought, 1990)
Orientalism has traditionally dominated discourse on the Middle East and thus obscured the human realities of the region. This monograph addresses the inadequacy and validity of existing theoretical perspectives on the Middle East. The critique presented offers Islam as a unifying constant rather than a sporadic phenomenon correlated to the flux of social, political and economic conditions and argues that Islam should be conceptually incorporated into any analysis of the region. The book defines the essence of Islamic civilization and highlights aspects of the colonial encounter as a background for understanding contemporary dynamics. Against a subtle leitmotiv of contrasting imagery, it profiles the Islamic view of the state, the role of the faith as well as that of the community. Useful distinctions are made between the Islamic and Western approaches to the area which should prove illuminating to both the area specialist and the lay reader.